Work Experiences of Emergency Medical Technicians in Emergency Care Services: A narrative Literature Review - Misbahuddin Azis; Novita Kurnia Sari (Jurnal Ners, 2026)
Abstract Background: Emergency Medical Technician (EMT) is a highly qualified medical practitioner, trained through accredited allied health education programs, to provide immediate basic life support to individuals in high-stress emergencies. Over the years, various strategies have been proposed to improve EMT performance, however, there remains a need for systematic evaluation of these strategies to identify the best practices and inform policy decisions. Methods : A systematic literature search was conducted across three databases Scopus, PubMed, and google scholar using the keywords “Emergency medical technician AND Paramedic OR work experience AND occupational experience” for articles published between 2021 and 2026. Article selection adhered to the PRISMA flow diagram, resulting in 7 final articles for analysis. Results: The findings identified five main issues related to emergency medical tehcnician work experience: 1) systemic pressures, 2) observational method dominance, 3) multidimensional burnout, 4) contextual and group vulnerabilities, and 5) implications for patient care quality. Conclusions: This study highlight the need for policies focused on proportional workload management, strengthening managerial support, and integrating mental health support in the workplace. Investing in staff well-being is a key strategy to maintain service quality and safety, underscoring the need for evidence-based policies guided by Maslach's burnout theory and the Job Demand–Resources Model, which should be continuously developed and evaluated. Keywords: Emergency medical technician, narrative literature review, occupational experience, paramedic, work experience